1982
DOI: 10.1002/jmv.1890090205
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human cytomegalovirus‐specific iga antibodies in colostrum by enzyme‐linked lmmunosorbent assay (elisa)

Abstract: Fifty women were examined after delivery for the prevalence of antibodies to human cytomegalovirus in colostrum and sera. Eighty percent of them had specific CMV IgG antibodies in the sera, as determined by the immunoperoxidase antibody to membrane antigen (IPAMA) technique. Of the CMV-seropositive women, 60% had specific CMV IgA antibodies in high titer in the colostrum as determined by enzyme-linked immunosorbent assay (ELISA). In only two of the seropositive women were specific CMV IgA antibodies detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
1986
1986

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Perinatal CMV infections were shown to be either asymptomatic or associated with respiratory syndromes, pneumonitis or hepatitis [Andersen et al, 1972;Stern, 1975;Granstrom et al, 1977;Ahlfors et al, 1978;Stagno et al, 1981;Panjvani and Hanshaw, 19811. CMV excreted in the endocervix, breast milk, and saliva were suggested to be the source of perinatal CMV infections and virus perpetuation [Hayes et al, 1972: Numazaki et al, 1970Reynolds et al, 1973: Granstriim et al, 1977Cabau et al, 1979;Stagno et al, 19811. Recently, in this laboratory, Pinku et al [1982] have demonstrated specific CMVIgA antibodies in colostrum of 60% of CMV seropositive women by enzyme-linked immunosorbent assay (ELISA). Both congenitally and perinatally infected children excrete CMV in the urine and nasopharynx for several months or even years despite high levels of' circulating antibody, and serve as a constant reservoir for horizontal spread of infection [Hanshaw et al, 1965: Lang, 1975Cabau et al, 19791.…”
Section: Introductionmentioning
confidence: 98%
“…Perinatal CMV infections were shown to be either asymptomatic or associated with respiratory syndromes, pneumonitis or hepatitis [Andersen et al, 1972;Stern, 1975;Granstrom et al, 1977;Ahlfors et al, 1978;Stagno et al, 1981;Panjvani and Hanshaw, 19811. CMV excreted in the endocervix, breast milk, and saliva were suggested to be the source of perinatal CMV infections and virus perpetuation [Hayes et al, 1972: Numazaki et al, 1970Reynolds et al, 1973: Granstriim et al, 1977Cabau et al, 1979;Stagno et al, 19811. Recently, in this laboratory, Pinku et al [1982] have demonstrated specific CMVIgA antibodies in colostrum of 60% of CMV seropositive women by enzyme-linked immunosorbent assay (ELISA). Both congenitally and perinatally infected children excrete CMV in the urine and nasopharynx for several months or even years despite high levels of' circulating antibody, and serve as a constant reservoir for horizontal spread of infection [Hanshaw et al, 1965: Lang, 1975Cabau et al, 19791.…”
Section: Introductionmentioning
confidence: 98%
“…Specific IgA antibodies to microbial antigens have been reported in a few cases only, e.g., to pili of Klebsiella pneumoniae (5); to Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, poliovirus, coxsackie B virus, echovirus, and influenza virus (8); to Mycobacterium leprae (19), and to cytomegalovirus (20). The exciting role of IgA antibodies to peptidoglycan is based on the fact that peptidoglycan, with the exceptions of the mycoplasmatales and the archaebacteria (30), may be regarded a kind of common antigen among bacteria and that the R-D-Ala2 sequence of the peptide subunit represents a specific antigen of clinically relevant gram-positive cocci.…”
Section: Downloaded Frommentioning
confidence: 99%